Synchrotron XRF spectroscopy for reading salt-encrusted cuneiform tablets - Mirko Surdi; Pieter Tack; Sylvia Lycke; Sebastian Schöder; Katrien De Graef (Scientific Reports)
Abstract Cuneiform tablets were a primary writing medium in the ancient Near East from the late fourth millennium BCE to the first century CE. Although these clay tablets were durable for daily use, prolonged burial over millennia has made them vulnerable to salt damage. Fluctuations in temperature and humidity cause the migration of salts to the surface of the tablets, damaging them and covering the inscriptions, making the text unreadable. Traditional preservation and restoration techniques, such as firing and tetraethyl orthosilicate (TEOS) treatments, although effective in making the text legible again, cause irreversible physicochemical alterations, compromising the historical integrity of the tablets. To address this issue, we used synchrotron radiation X-ray fluorescence (SR-XRF) spectroscopy to analyze cuneiform tablets covered by salts. This method enabled the recovery of previously unreadable texts without altering the nature of the tablets. Our findings highlight the importance of non-invasive methods for preserving and studying cuneiform tablets, maintaining their physicochemical integrity, and allowing for future analyses.